2000
DOI: 10.1111/j.1834-7819.2000.tb00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing practices by South Australian general dental practitioners

Abstract: The prescribing habits of a randomly selected approximately 10 per cent sample of South Australian general dental practitioners were obtained by postal questionnaire. Sixty‐eight (61 per cent) usable replies were received and analysed. Generally, there was an appropriate level of knowledge of antibiotic prescription. However, there was a tendency toward over‐prescription and a demonstrated lack of knowledge of the incidence of adverse reactions, development of multiresistant strains and prophylaxis against bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
100
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 20 publications
(11 reference statements)
8
100
1
2
Order By: Relevance
“…5 Multiple studies carried out across the world showed that antibiotics are not used prudently for various dental infections and it has lead to multiple complications including development of resistance. 6 It is high time to create awareness, find and bridge the gap about different dimensions of antibiotic uses including antimicrobial stewardship and inculcate a practice of rational uses of drugs in general and antibiotics in particulars among budding medical and dental practitioners who will be the torchbearers of tomorrow. 7,8 There are large number of studies to assess the KAP of medical students on antibiotic resistance as well as stewardship but few studies are there to measure the same in dental students.…”
Section: Introductionmentioning
confidence: 99%
“…5 Multiple studies carried out across the world showed that antibiotics are not used prudently for various dental infections and it has lead to multiple complications including development of resistance. 6 It is high time to create awareness, find and bridge the gap about different dimensions of antibiotic uses including antimicrobial stewardship and inculcate a practice of rational uses of drugs in general and antibiotics in particulars among budding medical and dental practitioners who will be the torchbearers of tomorrow. 7,8 There are large number of studies to assess the KAP of medical students on antibiotic resistance as well as stewardship but few studies are there to measure the same in dental students.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the last 10 to 15 years there has been a progressive return of serious antibiotic resistance. 3 This has been insidious and there has been a tendency for serious odontogenic infections to be dismissed in hospital practice as simple dental problems. The authors are aware of at least two deaths of patients whilst under treatment for odontogenic infections in major Australian teaching hospitals in the last few years.…”
mentioning
confidence: 99%
“…Only 22 per cent knew the correct incidence of allergy for penicillin with most under estimating the incidence of adverse events. 7 Recently the use of antibiotic prophylaxis for third molars has become controversial with reviews based on clinical studies, 8,9 rather than opinion, 10 challenging the value of antibiotic prophylaxis.…”
mentioning
confidence: 99%